Oxidative stress and exogenous constitutional obesity - O. A. Silizertseva; M. A. Darenskaya; L. V. Rychkova; I. N. Gutnik; T. A. Astakhova; L. I. Kolesnikova (Сибирский научный медицинский журнал)
The literature review is devoted to the problem of exogenous-constitutional obesity and the role of oxidative stress (OS) in this form of obesity. The issues of modern diagnostics and pathogenesis of exogenous-constitutional obesity are considered. The results of various studies devoted to the study of OS in obesity in both laboratory animals and humans are presented. Excess body weight is often accompanied by increased OS and subclinical systemic inflammation. The need to correct the antioxidant status of the body is a topical issue, an important part of which is an individual approach to the selection of agents and dosages in order to reduce the negative impact of free radicals at the cellular level. A significant problem is the lack of a single standard for determining OS parameters, which requires standardized laboratory equipment, in this regard, the choice of a specific method is a responsible step for a research specialist. In this area, there are still many questions that require more detailed study.